Peran Majelis Pengawas Daerah dan Notaris Penerima Protokol Terhadap Penyimpanan Protokol Notaris Yang Telah Berumur 25 Tahun - Dian Ayu Yuhana (Officium Notarium, 2021)
This study was conducted to analyze the role of the Regional Supervisory Council for the storage of Notary Protocol that is 25 years old and to identify the responsibilities of the Notary Protocol Recipients to the Notary Protocol that is 25 years old. The formulation of the problems in this research are first, what is the role of the Regional Supervisory Council on the storage of a Notary Protocol that is 25 years old? Second, how is the responsibility of the Notary Recipient of the Protocol to the Notary Protocol who is 25 years old? This type of research is empirical with a statutory approach, with juridical analysis. The results of this study conclude that, firstly, the role of the Regional Supervisory Council has not run properly because it is constrained by the facilities and infrastructure for storing Notary Protocols, secondly, the responsibilities of the Notary Recipient of the Protocol to the Notary Protocol that is 25 years old that it has received are to store, maintain, and take care in the way that the Protocols are kept safely that they are not easily damaged and lost because the Notary Protocol is a state archive that must be safeguarded.Keywords: Notary; notary protocol; regional supervisory councilAbstrakPenelitian ini dilakukan untuk menganalisis peran Majelis Pengawas Daerah terhadap penyimpanan Protokol Notaris yang telah berumur 25 tahun aserta mengetahui tanggungjawab dari Notaris Penerima Protokol terhadap Protokol Notaris yang berumur 25 tahun. Rumusan masalah dari penelitian ini, pertama, bagaimana peran Majelis Pengawas Daerah terhadap penyimpanan Protokol Notaris yang berumur 25 tahun? Kedua, bagaimana tanggungjawab Notaris Penerima Protokol terhadap Protokol Notaris yang berumur 25 tahun? Jenis penelitian ini adalah empiris dengan pendekatan perundang-undangan, dengan analisis yuridis. Hasil penelitian ini menyimpulkan, pertama, peran Majelis Pengawas Daerah belum berjalan sebagaimana mestinya karena terkendala sarana dan prasarana penyimpanan Protokol Notaris, kedua tanggungjawab Notaris Penerima Protokol terhadap Protokol Notaris yang berumur 25 tahun yang telah diterimanya yaitu menyimpan, menjaga, dan merawat agar Protokol-Protokol tersebut tetap tersimpan dengan aman agar tidak mudah rusak dan hilang karena Protokol Notaris merupakan arsip negara yang harus tetap ada.Kata Kunci: Majelis pengawas daerah; notaris; protokol notaris